Comparative transcriptomic analysis revealed novel potential therapeutic targets of traditional Chinese medicine (Pinggan-Qianyang decoction) on vascular remodeling in spontaneously hypertensive rats - Jiamei Yao; Cui Zhang; Yushu Yang; Xia Fang; Qiong Chen; Guangwei Zhong (BMC, 2021)
Abstract Background Both experimental and clinical studies have revealed satisfactory effects with the traditional Chinese formula Pinggan Qianyang decoction (PGQYD) for improving vascular remodeling caused by essential hypertension. The present study explored various therapeutic targets of PGQYD using mRNA transcriptomics. Methods In this study, rats were randomly divided into three groups: Wistar-Kyoto (WKY; normal control), spontaneously hypertensive (SHR), and PGQYD-treated rat groups. After 12 weeks of PGQYD treatment, behavioral tests were employed and the morphology of thoracic aortas were examined with hematoxylin-eosin (HE) and Masson staining and electron microscopy. The mRNA expression profiles were identified with RNA-Seq and quantitative real-time PCR to validate changes in gene expression observed with microarray analysis. The gene ontology and pathway enrichment analyses were carried out to predict gene function and gene co-expressions. Pathway networks were constructed to identify the hub biomarkers, which were further validated by western blotting and immunofluorescence analysis. Results After PGQYD treatment, the behavioral tests and histological and morphological findings of vascular remodeling were obviously meliorated compared with the SHR group. In the rat thoracic aorta tissues, 626 mRNAs with an exact match were identified. A total of 129 of mRNAs (fold change > 1.3 and P-value < 0.05) were significantly changed in the SHR group compared to the WKY group. Among them, 16 mRNAs were markedly regulated by PGQYD treatment and validated with quantitative real-time PCR. Additionally, target prediction and bioinformatics analyses revealed that these mRNAs could play therapeutic roles through biological processes for regulating cell metabolic processes (such as glycation biology), biological adhesions, rhythmic processes, and cell autophagy. The cellular signaling pathways involved in autophagy may be AGE-RAGE/PI3K/Akt/mTOR signaling pathway. Conclusion The present study provides novel insights for future investigations to explore the mechanisms by which PGQYD may effectively inhibit vascular remodeling by activating the AGE-RAGE/PI3K/Akt/mTOR signal pathway in cell autophagy biology.